The 1951 Deportation Operation of Lithuanians Called “Autumn”: Deportations from Eišiškės District - Balkytė , Dalia (Genocidas ir rezistencija, 2015)
One of the main features of the Stalinist period in Lithuania was forced deportation of Lithuanians. Back in the times of the Tsarist Russia, the authorities practiced large-scale deportations (forced resettlement from the place of residence to other areas). Over a few decades of the Soviet rule, the mass resettlement of people became a standard practice. Deportations were initiated by the political leadership and were planned and carried out by repressive structures. Since 1941, 30 deportation operations were carried out in Lithuania occupied by the Soviet Union. The USSR leadership treated deportations as a state task of great political importance. Deportations were aimed at breaking the armed resistance of the population against the occupying power, implementing political and economic goals of Sovietisation of Lithuania, and using free labour force in sparsely populated areas of the Soviet Union. People were relocated by force from their native land to remote regions, where they lived under totally unaccustomed conditions and lost all their property and possessions. The deportees had no right to leave their new places of residence (special settlements) and were under the threat of criminal charges for the breach of this prohibition. The article analyses the deportation of Lithuanians from Eišiškės District of Vilnius Region in autumn 1951 during the operation called “Autumn”. Eišiškės District, like several other districts of the Lithuanian SSR, was a multi-ethnic district, Poles being a large ethnic group in the area. The 1951 deportation operation “Autumn” was carried out in two stages: in September, families of partisans and their supporters were deported and in October, affluent farmers with families and relatives who lived and managed the farms together were deported. This deportation was one of the largest operations of this kind in Lithuania. On 21 September, 33 people (10 families), of which 12 were Polish, were deported. On 3 October, 267 people (71 families), of which 177 Polish, were deported. During this operation the residents of Lithuania were deported to Krasnoyarsk Krai and Irkutsk Oblast. Forced resettlement of the population was not carried out on the basis of the nationality. It served as means to dispose of the people who socially or politically did not satisfy the occupation authorities. Lithuanian or Polish partisans or members of their families, as well as affluent farmers were perceived as dangerous by the Soviet government. The deportees were used as cheap labour force in the regions of the USSR. The operation “Autumn” in Eišiškės District was a standard operation, except that the district was multi-ethnic. The archival documents show a uniform pattern of such operations: an operation plan was drawn according to a single scheme, lists of people to be exiled were then prepared, operational groups to execute the plan were formed, forces required to execute the deportation were estimated, etc.